2019
DOI: 10.1016/j.nuclphysb.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Y junction of quantum spin chains

Abstract: We study a Y junction of spin-1/2 Heisenberg chains with an interaction that breaks both time-reversal and chain exchange symmetries, but not their product nor SU(2) symmetry. The boundary phase diagram features a stable disconnected fixed point at weak coupling and a stable three-channel Kondo fixed point at strong coupling, separated by an unstable chiral fixed point at intermediate coupling. Using non-abelian bosonization and boundary conformal field theory, together with density matrix renormalization grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 99 publications
(243 reference statements)
0
17
0
Order By: Relevance
“…Remarkably, for a special value J χ = J c χ , one finds an ideal chiral fixed point where incoming spin currents are perfectly rerouted to the next chain in rotation, without any backscattering. For → ∞, the chiral point is unstable as it corresponds to a BCFT critical point [35,36]. We here show from density matrix renormalization group (DMRG) simulations that in networks of finite-length spin chains, the chiral fixed point remains present.…”
Section: Arxiv:190600807v1 [Cond-matstr-el] 3 Jun 2019mentioning
confidence: 79%
See 2 more Smart Citations
“…Remarkably, for a special value J χ = J c χ , one finds an ideal chiral fixed point where incoming spin currents are perfectly rerouted to the next chain in rotation, without any backscattering. For → ∞, the chiral point is unstable as it corresponds to a BCFT critical point [35,36]. We here show from density matrix renormalization group (DMRG) simulations that in networks of finite-length spin chains, the chiral fixed point remains present.…”
Section: Arxiv:190600807v1 [Cond-matstr-el] 3 Jun 2019mentioning
confidence: 79%
“…A single Y junction of spin-1/2 Heisenberg chains has been studied in Refs. [35,36]. The boundary conditions at this junction can be controlled by tuning a three-spin interaction J χ , see Fig.…”
Section: Arxiv:190600807v1 [Cond-matstr-el] 3 Jun 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…This phase diagram exhibits a variety of phases, including the chiral phase which appears in a relatively weak magnetic field regime [15]. Very recently, studying the so-called Y junctions made of spin-1/2 Heisenberg chains, it has been shown that a network of these junctions, with uniform coupling constants, may realize chiral spin liquid phases [16,17]. Remarkably, a controlled analytical investigation of these chiral spin liquid states may be realized by means of a honeycomb lattice of Heisenberg spin-1/2 chains, with three-spin Y junction interactions [18].…”
Section: Introductionmentioning
confidence: 99%
“…18,21,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] The ground state properties of Y junctions have also been explored using density matrix renormalization group (DMRG) techniques. [51][52][53] A study of TDOS using bosonization technique for spinless fermion was reported by Agarwal et al in Ref. [18] and a collection of FPs (stable for g > 1) were identified which showed enhancement of TDOS in the zero energy limit and the effect was attributed to an Andreev-like reflection off the junction.…”
Section: Introductionmentioning
confidence: 99%